Application of Team Teaching Learning Methods on Mathematics Learning Results in Vocational High School Country Abdi Binjai - Makmur Syukri; Amiruddin Siahaan; Muhammad Isa; Sartika Hutasuhut (Edumaspul: Jurnal Pendidikan, 2022)
Team teaching in Indonesia has been implemented and has an impact on student learning processes and success in learning. Team Teaching has an impact on education in Indonesia because applying this method in schools can help the success of the teaching process. This study aims to determine the application of the team teaching learning method to the learning outcomes of mathematics subjects. The method to be used is by experiment. The study was conducted on students of Class X. This study used two classes for the study of 75 students, class A as a control class with the lecture method and class B as an experimental class with the team teaching method, from the two methods used, researchers will see and compare the learning outcomes student. Based on the research obtained as follows: (1) both data are normal and homogeneous, (2) there are differences between students whose learning uses the team teaching method and the lecture method. The results showed that students whose learning activities used the team teaching method could improve learning outcomes in mathematics.